Glove-shaped Foam with Negative Pressure Wound Therapy for Skin Graft Fixation on the Hand - Eriko Yoshida, MD; Shogo Maeda, MD, PhD; Takashi Nuri, MD, PhD; Hiroyuki Iwanaga, MD; Yuka Hirota, MD, PhD; Asuka Takei, MD; Chizuru Umeda, MD; Kurumi Fujiwara, MD; Koichi Ueda, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2023)
Tie-over bolster dressing has been the gold standard for skin graft immobilization. However, skin grafting onto the hand remains challenging. To prevent shearing of the skin, joint fixation with Kirschner wire and casting is often required. However, wire fixation through the joint can disrupt finger growth and cause joint contracture, especially in pediatric patients. So, we performed graft fixation with negative pressure wound therapy (NPWT). The use of NPWT with skin grafting has recently been reported. Previous studies have reported that NPWT can provide even pressure on irregular wounds and in highly mobile areas. However, application of NPWT in the digital region often results in air leaks. This report includes four patients who required skin grafting on the hand. All patients received skin grafts in the affected area. Graft fixation was performed with NPWT. A glove-shaped form was designed. The hand was encased on the ventral and dorsal sides and small pieces of foam were placed between the fingers. The fixation was maintained for 7 days at a pressure of −50 to −80 mmHg. None of the cases had air leak requiring reattachment of the system and graft take was successful in all cases without any complications. The NPWT “glove-shape” technique enabled maintenance of average negative pressure for all skin grafts on the hand. This technique does not require joint fixation and may help to prevent growth disturbance and joint contracture.